A new genus of spider wasps (Hymenoptera, Pompilidae) from the Seasonal Semideciduous forests of southern Brazil - Festa, Fernanda Albino; Faria, Luiz R. R.; Waichert, Cecilia (Zootaxa, 2025)
A new genus and species of spider wasp (Pompilidae) are described based on male and female specimens collected in the Seasonal Semideciduous forests of Brazil. Nhanduara pytun Festa, Faria & Waichert, gen. et sp. nov. belongs to the tribe Ageniellini (Pepsinae), which is now recognized as comprising nine genera in the Neotropical Region. Relevant morphological structures are illustrated, and the taxonomic position of the genus is discussed.